Heavy metals accumulation in Nerium oleander leaves across urban areas in Setif region, Algeria - MOHAMED AMINE KOUCIM; Amina Belguidoum; TAKIA Lograda; Messaoud Ramdani (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Koucim MA, Belguidoum A, Lograda T, Ramdani M. 2021. Heavy metals accumulation in Nerium oleander leaves across urban areas in Setif region, Algeria. Biodiversitas 22: 3083-3091. Pollution by Metallic trace elements (MTE) has become one of the most serious environmental problems resulting from human activity. Plants, which are the base of the food chain, can take up MTE from the soil solution; hyper-accumulators can store high levels of heavy metals in their aerial parts at high concentrations. These plants can be used in phytoremediation. This study aimed to investigate the accumulation of MTE in the leaves of Nerium oleander to monitor environmental pollution of several areas in the province of Setif, Algeria. The samples of N. oleander leaves were collected from 20 urban areas in Setif Province. The concentrations of seven metallic trace elements (Cd, Mn, Pb, Sb, Cu, Bi and Fe) were determined using Flame Atomic Absorption Spectrophotometry (AASF). The results show that the concentrations of heavy metals in the leaves of N. oleander, in general, were very high, far exceeding the certified standard ranges. The order of MTE in the leaves was found as follows: Mn> Sb> Bi> Pb> Fe> Cu> Cd. Our findings indicate that although N. oleander showed a significant capacity to accumulate MTE, the urban areas of Setif province were highly polluted by heavy metals. The presence of metal ions in the aerial parts of the plant indicates that N. oleander is a hyper-accumulator of metals with tolerance to Mn, Sb, and Pb, and can be used as a bio-monitor. This opens up prospects for its application for soil phytoremediation.